Strengthening Digital Marketing Capacity For Msmes In Cileungsi To Accelerate Business Growth - Eryandi, Eryandi; Eliza, Eliza; Budiarti, Erna; Simbolon, Merintan Berliana; Haryadi, Rofiq Noorman (Pasundan Community Service Development, 2025)
Digital marketing has become a crucial aspect in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the era of globalization and digitalization. This article aims to discuss the efforts in strengthening the digital marketing capacity of MSMEs in Cileungsi, which plays a key role in accelerating their business growth. Various digital marketing strategies, such as the use of social media, search engine optimization (SEO), and digital advertising, have proven effective in expanding market reach and increasing the visibility of MSME products. However, many MSMEs in Cileungsi still face challenges related to limited technological knowledge and budget constraints. Therefore, training and mentoring on how to utilize the appropriate digital platforms and relevant marketing tools are essential to overcoming these obstacles. This article also highlights the importance of using data analytics to measure the effectiveness of digital marketing campaigns and build better customer relationships through digitalization. With strengthened digital marketing capacity, MSMEs in Cileungsi are expected to tap into broader market potential, improve competitiveness, and accelerate their business growth sustainably.